2018
DOI: 10.1016/j.cmi.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of tigecycline in the management of Clostridium difficile infection: a retrospective cohort study

Abstract: Adding tigecycline to CDI standard therapy did not increase the clinical cure nor reduce the rate of CDI recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Moreover, three retrospective cohort studies failed to demonstrate a beneficial effect of adjunctive tigecycline CDI treatment on patients outcome in comparison to standard treatment alone ( 145 147 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, three retrospective cohort studies failed to demonstrate a beneficial effect of adjunctive tigecycline CDI treatment on patients outcome in comparison to standard treatment alone ( 145 147 ).…”
Section: Resultsmentioning
confidence: 99%
“…These data support the use of tigecycline in complicated and severe C difficile infection. Two retrospective studies confirm the safety of the drug in severely infected patients118 but failed to show an improvement compared with standard therapy in clinical cure or recurrence rate 119. If tigecycline is used to treat severe infections, it should be considered a substitute to metronidazole as adjunctive therapy to vancomycin.…”
Section: Treatmentmentioning
confidence: 99%
“…84 Recently published retrospective studies have shown conflicting results regarding the efficacy of tigecycline for fulminant CDI. 85,86,87,88 Because of the poor outcomes associated with fulminant CDI, there may be a role for adjunctive tigecycline. 84 Consideration of surgical intervention and faecal microbiota transplantation (FMT) in such settings is also indicated.…”
Section: What Are the Recommended Treatment Options For An Initial Episode Of Fulminant Clostridioides Difficile Infection?mentioning
confidence: 99%